The Application of Communication Privacy Management Theory to Health Information on COVID-19 Through Social Media among Young Women - Diponegoro, Muhammad Agung; Utari, Prahastiwi; Rahmanto, Andre Noevi (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2022)
Background: Social media is open to inappropriate access, misuse, and disclosure of health data. The increasing public anxiety about the COVID-19 outbreak was triggered by the spread of hoax news. This research applies the framework of Communication Privacy Management Theory (CPM) for analyzing the disclosure of health information about COVID-19 through social media. This study aimed to explore health information on COVID-19 through social media in young women.Subjects and Method: This was a qualitative study with a phenomenological approach. The study was conducted in Surakarta, Central Java, from March - August 2021. Study participantss involving 10 women aged 23-24 year as participants. The study dimensions consist of privacy ownership within the boundaries of privacy, privacy control through privacy rules, and turbulence of health information privacy regarding COVID-19. The data were collected by literature review and in-depth interview. Results: Privacy ownership is privacy right and can be disclosed by the authorized only. COVID-19 patients’ status should be disclosed for tracing and finding convalescence plasma donor. Disclosure is useful to increase knowledge, correct information, influence people, and appeal preventive and curative attempts. Disclosure is useful to increase knowledge, correct information, influence people, and appeal preventive and curative attempts. Disclosure should consider different genders, situations, expectations, cultures, situational and condition demand, and ethics. Criteria of privacy border relate to urgency and need. Permeability always changes, and situation can lead to private border removal. Posting privacy information needs to crosscheck truth, consider privacy right, and privacy setting. Privacy control is required to avoid abuse. Privacy turbulence results from private rule infringement, private and public information bias, hoax, private information leakage, gossip, etc. Socialization, system improvement and supervision, and sanction imposition are needed.Conclusion: CPM theory can be used to explore private information on COVID-19.Keywords: communication privacy management, disclosure, social media, phenomenologyCorrespondence: Muhammad Agung Diponegoro. Masters Program in Communication Sciences, Faculty of Social and Political Sciences, Universitas Sebelas Maret Email: abdiaghoenk@gmail.com. Mobile: +62214281288.Journal of Health Policy and Management (2022), 07(01): 14-23https://doi.org/10.26911/thejhpm.2022.07.01.02